Performance study of iSCSI-based storage subsystems. - Lu, Yingping (IEEE Communications magazine)
iISCSI is emerging as an end-to-end protocol for transporting storage I/O block data over IP networks. By exploiting the ubiquitous Internet infrastructure, iSCSI greatly facilitates remote storage, remote backup, and data mirroring. This article evaluates the performance of two typical iSCSI storage subsystems by measuring and analyzing block-level I/O access performance and file-level access performance. In the file-level performance study, we compare file access performance in an NAS scheme with that in an iSCSI-based SAN scheme. Our test results show that Gigabit Ethernet-based iSCSI can reach very high bandwidth, close to that of a direct FC disk access in block I/O access. However, when the iSCSI traverses through longer distance, throughput relies heavily on the available bandwidth between the initiator and the target. On the other hand, the file-level performance shows that iSCSI-based file access (SAN scheme) provides higher performance than using NFS protocol in Linux and SMB protocol in Windows (NAS scheme). However, the advantage of using iSCSI-based file accesses decreases as the file size increases. The obtained experimental results shed some light on the performance of applications based on iSCSI storage.